ENHANCING DETECTION THROUGH ADVANCED COLLABORATION BETWEEN FORENSIC MEDICINE AND LABORATORIES - A CRITICAL INSIGHT - Khalid Mujahed Alwaily, Mohammed Mahdi Ali Jali, Ali mana muslih Alabbas, Hadi Mohammed Hussain Al sharyah, Mohammed Ahmed Mohammed ALZabadin, Mohammed Musfer Mana AlHotelah, Hadi Abdullah Hadi Al Hokash (Chelonian Research Foundation, 2023)
The dynamic interplay between forensic medicine and laboratory sciences serves as the cornerstone for modern investigative processes, with their collaboration pivotal in the quest for justice. This article embarks on a critical examination of the current landscape of forensic investigations, shedding light on the synergistic potential that lies in the enhanced cooperation between forensic medicine and laboratory techniques. It delves into the evolving challenges and innovative practices that characterize this interdisciplinary nexus, highlighting the indispensable role of technology and methodological advancements in overcoming barriers to detection. Through a critical lens, the article reviews case studies that exemplify successful collaborations, while also reflecting on instances where the lack of integration hindered judicial outcomes. The discourse extends to future directions, emphasizing the necessity for continuous innovation, education, and policy evolution to foster a more cohesive and effective forensic ecosystem. This article advocates for breaking down disciplinary silos to harness the full potential of forensic science in the pursuit of truth and justice. Keywords: Forensic Medicine, Laboratory Techniques, Interdisciplinary Collaboration, Technological Advancements, Detection Capabilities, Forensic Investigation, Justice, Innovation, Education, Policy Evolution